The Effect of Stress, Emotional Intelligence, and Recovery Elasticity on Clinical Performance of Nursing College Students - minjeong, Kang; A yeon, Kim; yeonju, Woo; jimin, Lee; jihye, Lim; sua, Chae; byeongjun, Park (Universitas Muhammadiyah Yogyakarta, 2022)
Introduction: this study seeks to identify the relationship between stress and resilience, emotional intelligence, and clinical performance of nursing college students, and to understand the impact of these variables on clinical performance. Purpose: First, the stress, resilience, and emotional intelligence of nursing college students identify the degree of clinical performance. Second, we identify the differences in stress, resilience, emotional intelligence, and clinical performance according to the general characteristics of nursing college students. Third, identify the correlation between stress, resilience, emotional intelligence and clinical performance of nursing college students. Fourth, identify factors that affect clinical performance of nursing college students. Methodology: This study was conducted on 95 nursing students in the third and fourth grades of Daegu University. The subjects of the study were third and fourth grade students with internship experience. Findings: Clinical performance is emotional intelligence (B=.172, p=0.034), recovery elasticity (B=.481, p=0.001). In other words, the higher the emotional intelligence and resilience, the higher the clinical performance. Implication: Nurses' clinical performance is an important concept that directly affects nursing and hospital-wide efficiency (Park, 2007) , and it is urgent to identify and improve clinical performance and professional skills (Kim, 2020) . Nursing college students develop clinical performance skills to integrate overall nursing knowledge and practice through clinical practice, apply communication skills and basic nursing skills in practice, learn problem-solving skills, and develop value systems as professional nurses.